Peran Teknologi Dalam Mendukung Produktivitas Dan Kualitas Hidup Masyarakat - Riska Rismawati; Ade Fricticarani; Muhamad Hakim Abdurrahman (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2026)
The rapid growth of information and communication technology in recent years has significantly changed the daily routines and socio-economic activities of modern society. This quantitative study was conducted to analyze and directly test how the use of information technology influences work productivity efficiency as well as the overall quality of life. Employing an explanatory causal research design, primary data were gathered through structured questionnaires measured on a 5-point Likert scale distributed to 250 respondents. The sample was drawn using a simple random sampling technique across urban and surrounding suburban areas. Prior to hypothesis testing, the research instruments were confirmed to meet valid criteria through item validity testing and Cronbach's Alpha reliability evaluation. A series of classical assumption tests including normality, multicollinearity, and homoscedasticity were also fulfilled to ensure the validity of the multiple linear regression model.  Inferential data analysis revealed that information technology usage has a positive and significant impact, both simultaneously and partially, on boosting work productivity F=84.12;p<0.001 and improving quality of life F=62.45;p<0.001. Fast access to data and workflow automation emerged as key factors in accelerating daily routines. These findings emphasize that digital devices serve not merely as entertainment or interpersonal communication tools, but as vital supports for work efficiency and personal well-being. Therefore, expanding internet infrastructure and digital literacy programs is necessary to ensure these technological benefits are evenly distributed across all segments of society.   Keywords: Information Technology; Work Productivity; Quality of Life.